2009
DOI: 10.1007/s11244-008-9160-6
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Production from Catalytic Fast Pyrolysis of Biomass-Derived Feedstocks

Abstract: The conversion of biomass compounds to aromatics by thermal decomposition in the presence of catalysts was investigated using a pyroprobe analytical pyrolyzer. The first step in this process is the thermal decomposition of the biomass to smaller oxygenates that then enter the catalysts pores where they are converted to CO, CO 2 , water, coke and volatile aromatics. The desired reaction is the conversion of biomass into aromatics, CO 2 and water with the undesired products being coke and water. Both the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
391
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 638 publications
(444 citation statements)
references
References 43 publications
12
391
1
6
Order By: Relevance
“…The formation of aromatic hydrocarbons in OLP supported the hypothesis that the oxygenated compounds, particularly substituted phenols, in the pyrolysis oil can be converted into aromatic hydrocarbons by dehydroxylation, decarbonylation, and decarboxylation with the HSZM-5 catalyst (Carlson et al 2009;Zhao et al 2010;Cheng and Huber 2011). In addition, as the pyrolysis oil contained some acids, alcohols, aldehydes, ketones and esters, it was suggested that during the conversion of these compounds, olefins were formed as intermediate products, and they underwent a variety of further reactions to yield aromatic hydrocarbons (Adjaye and Bakhshi 1995a).…”
Section: Content Of Gasoline-range Aromatics In Olpsupporting
confidence: 53%
“…The formation of aromatic hydrocarbons in OLP supported the hypothesis that the oxygenated compounds, particularly substituted phenols, in the pyrolysis oil can be converted into aromatic hydrocarbons by dehydroxylation, decarbonylation, and decarboxylation with the HSZM-5 catalyst (Carlson et al 2009;Zhao et al 2010;Cheng and Huber 2011). In addition, as the pyrolysis oil contained some acids, alcohols, aldehydes, ketones and esters, it was suggested that during the conversion of these compounds, olefins were formed as intermediate products, and they underwent a variety of further reactions to yield aromatic hydrocarbons (Adjaye and Bakhshi 1995a).…”
Section: Content Of Gasoline-range Aromatics In Olpsupporting
confidence: 53%
“…However, this process converts any C1-C5 oxygenates, representing as much as half of the carbon in bio-oil, to C1-C5 hydrocarbons that are too volatile for liquid fuels (Resasco, 2011). Another straightforward approach is to "crack" the pyrolysis vapors using acidic zeolite catalysts into light olefins and aromatic hydrocarbons (primarily benzene, toluene, and o/m/p-xylene) (Bridgwater, 1994;Carlson et al, 2008Carlson et al, , 2009). This approach is appealing because of the lack of an external H2 requirement and the simplicity of the product streams.…”
Section: <1-3mentioning
confidence: 99%
“…Pyrolysis with the biomass-to-catalyst ratio of 1:1 ( Figure 6) promoted the production of low-molecular-mass phenolics to a large extent, while high-molecular-mass phenolics were increased or decreased depending on the species. This result is attributed to promoted decomposition of lignin to phenolics and of high-molecular-mass phenolics to low-molecular-mass phenolics or aromatics owing to deoxygenation (dehydration, decarbonylation, and decarboxylation) and cracking occurring on the acid sites of the catalysts [7,18]. When the catalyst dosage was increased further (Figure 7), the conversion of high-molecular-mass phenolics to low-molecular-mass phenolics was more evident.…”
Section: Resultsmentioning
confidence: 99%